Odpowiedzi

2009-11-08T16:33:03+01:00
A) (x+1)(x+2)=x²+2x+x+2=x²+3x+2
b)(3a+4)(a-5)=3a²-15a+4a-20=3a²-11a-20
c)(2t+1)(1-3t)=2t-3t²+1-3t=-t-3t²+1
d)(3ab-7)(3-7ab)=6ab-21a²b²-21-49ab=-43ab-21a²b²-21
e)(x+y)(5x+6y)=5x²+6xy+5xy+6y²=5x²+11xy+6y²
f)(x+5y)(7x-y)=7x²-xy+35xy-5y²=7x²+34xy-5y²
g)(2x⁴-y)(x⁴+y)= 2x⁸+2x⁴y-x⁴y-2y=2x⁸+x⁴y-2y
h) (ab-a)(2ab+6a)= 2ab²+6a²b-2a²b-6a²=2ab²+4a²b-6a²
Pozdrawiam:)
2009-11-08T16:34:54+01:00
A)=2x*2x=4x
b)=7a*(-4a)=28a
c)=3t*(-2t)=6t
d)=(-4ab)*(-4ab)=16ab
e)=xy*(5x+6y)=6x+7y=13xy
f)=5xy*6xy=30xy
g)=16x-y)*4xy=64x
h)=b*(8a+2b)=10ab

Pozdro ;)
2009-11-08T16:36:47+01:00
A) x^2+2x +x+3= x^2+3x+3
b)3a^2-15a+4a-20=3a^2-11a-20
c) 2t-6t^2+1-3t=-6t^2-t+1
d) 9ab-21a^2b^2-21+49ab=21a^2b^2+58ab-21
e)-5x^2-6xy+5xy+6y^2=-5x^2+6y^2-xy
f) 7x^2-xy+35xy-5y^2=7x^2-5y^2+34xy
g) 2x^8+2x^4y-x^4y-y^2=2x^8-y^2+x^4y
h) 2a^2b^2+6a^2b-2a^2b-6a^2=-6a^2+6a^2b